The Influence Of Price, Brand Image And Promotion On The Decision To Buy Milk SGM At Karangmalang Sragen - Bagus Karya Manunggal; Basuki Sri Rahayu (Journal of Indonesian Science Economic Research, 2019)
This study aims to find out, analyze, and provide empirical evidence that there is an effect of brand image, price, and promotion on the decision to buy SGM milk at KarangmalangSragen. The population in this study was SGM milk buyers at KarangmalangSragen November 2018. 100 people were selected as research samples by random sampling method. The analysis technique in this study consisted of testing instruments, validity, reliability, classic assumption tests, multiple linear regression analysis, t test, F test, and R2 test. The results of multiple linear regression research showed that, Brand Image, Price and Promotion had a positive effect Regarding the decision to purchase SGM milk at KarangmalangSragen. The results of the t test show that the Brand Image, Price, and Promotion in fact have a significant effect on the decision to purchase SGM milk at KarangmalangSragent.The results of the F test show that the variables of Brand Image, Price and Promotion simultaneously have a significant effect on the decision to purchase SGM milk at KarangmalangSragen. The R2 (coefficient of determination) results are 0.584 which means that the purchase decision is explained by the Brand Image variable, Price and Promotion of 58.4% while the remaining 41.6% is explained by other variables not included in this study such as Brand Image, Consumer Motivation, Product Quality, Service, Location.